Webcomics malvados: tecnologia e interação nos quadrinhos de André Dahmer - Santos, Rodrigo Otávio dos (2010)
The purpose of the present work is to think over the relations between technology and society, more specifically regarding comics and the internet. To that end, the webcomic Malvados, whose author, André Dahmer, in part of his work think about the internet from the society's, the user's of the available online tools point of view, was researched. In the development of this research, the history of both, comics and webcomics, was presented. In addition, the caracteristics of this media and how the structure of the internet affects some of these characteristics at the same time it creates others, which exist only in the virtual world, were analysed and discussed. With this theoretical basis, the Dahmer's comics strips, particulary those reflecting the use of the internet tools by the individuals, were analysed, taking into account how the artist sees the society and its "multimediatic" reflexes.